Fatty acid composition of fresh, smoked and dried anchovies (Stolephorus commersonii) - Liban, Marjorie V.
ABSTRACT Fish and other marine animals contain high amounts of polyunsaturated fatty acids that are believed to be beneficial to human health. The fat content and fatty acid composition of long-jawed anchovy (Stolephorus commersonii) and its products was evaluated in this study since it is one of the most commonly consumed fish species in the Philippines. The data gathered showed that fresh, smoked and dried anchovies have fat contents of 8.06 ± 0.64, 14.40 ± 0.52 and 12.86 ± 0.79 percent (wet basis), respectively. Among the C12-C18 fatty acids, palmitic acid was the most predominant , yielding 26.1%, 39.6% and 26.6% for the fresh, dried and smoked anchovies, respectively. As for the unsaturated fatty acids, palmitoleic acid was the most predominant for the fresh, yielding 13.3% and oleic acid for both dried and smoked anchovies consisting of 13.9% and 13.2%, respectively. The trends in the variation of the amount of fatty acid contents of the three samples are difficult to assess since there are a lot of factors to be considered such as the processing itself and the source of the samples. However, despite the lack of control for the processed samples, it can be concluded that long-jawed anchovies have great potential as a source of quality fatty acids whether fresh or processed.